What's Left in the City? What's Right in the Hinterland?: Urban Political Economy in Contemporary Latin America - Goldfrank, Benjamin; Schrank, Andrew (Conference Papers – American Political Science Association, 2006)
This paper accounts for the initial divergence and subsequent convergence of two types of urban political economy-neoliberal and socialist-in late twentieth and early twenty first century Latin America. Part 1 identifies the ideological differences between the two types of city as well as their implications for public policy. While neoliberal cities prioritize accumulation, and therefore use tax breaks, regulatory rollbacks, and the repression of organized labor to attract and retain foreign direct investment, their socialist rivals prioritize distribution, and therefore use social funds,microcredit arrangements, and participatory institutions to employ and empower their citizens. Part 2 treats the emergence of municipal neoliberalism as a secondary city or hinterland reaction to the growth of urban primacy or bias in the 1960s and 1970s. While industrial interests in population centers like Mexico City and São Paulo reaped the rewards of import-substituting industrialization, and therefore organized to defend their gains, their agro-commercial rivals paid a high price for tariffs and foreign exchange controls, and therefore deployed free trade zones (and similar incentives) in places like Chihuahua and Salvador to offset or compensate for the growth of urban primacy. Part 3 traces the origins of municipal socialism to the breakdown of ISI and the accompanying debt crisis in the late twentieth century. While neoliberal municipalities had already embraced the world market, and therefore welcomed structural adjustment at the national level, their socialist rivals feared globalization, and responded with a variety of compensatory measures of their own designed to increase the "social wage" not only in Mexico City and São Paulo but in other major cities like Caracas, Montevideo, and Lima. And, finally, Part 4 concludes by offering a Polanyian interpretation of the seemingly odd convergence of neoliberal and socialist municipalities today-suggesting that, whatever their ideological preferences, municipal authorities must balance accumulation with distribution if they are to survive and prosper in a globalized world. ..PAT.-Unpublished Manuscript
Political Science
Keywords: EPZ; Latin America; Latin America - politics & government; cities & towns; foreign investments; local politics; neoliberalism; participatory budgeting; political planning; socialism